EVALUATION OF EFFECT OF GUIDANCE AND COUNSELING PROCEDURES ON THE PERFORMANCE OF LEARNERS WITH EMOTIONAL AND BEHAVIOR DISORDERS IN KIMILILI SUB COUNTY, KENYA - Lwangale, Dr. David Wafula Lwangale; Nabiliki, Catherine Nanjala; Sichari, Dr. Manson (IJRDO- Journal of Educational Research, 2021)
The purpose of this study was to look at influence of guidance and counseling procedures on academic performance of learners with Emotional and behaviors disorders in primary schools in Kimilili Sub-County, Kenya. This study was based on three theories of learning. They include; Behavioral theories, social learning theory and motivation theory. This study was guided by a descriptive survey design. The study targeted head teachers, teachers from primary schools, Sub-County quality assurance officers and EARC officer in the sub-county of Kimilili. The research used cluster and random sampling technique for the head teachers and teachers from cluster schools. This ensured each member of the target population has the equal and independent choice of being included in the sample. Purposive sampling was on DAQSO and EARC officer to be able to collect specific information or data for learners with EBD in the sub-county. Data was edited to check for completeness and consistency. The incomplete responses were assigned a mean of other questions measuring that particular variable. The coding, analyzing, categorizing and keying in the data was organized under different variables and then frequency distribution measure of central tendency and percentage used. The study found out that the awareness of the existence of EBD learners is the start point of the road map of their assistance to achieve their academic potentials. Learners who are regarded as stubborn should be assisted to change their character through guidance and counseling programme. Punishment may not yield desired results in handling EBD learners. The school should create friendly environment for instruction of EBD learners. Teachers had a passion for EBD learners. This was a pointer towards the effectiveness of guidance and counseling in helping EBD learners. The effectiveness of guidance and counseling depends on the procedures. School discipline contributes a lot the management of EBD learners. The challenges of implementing guidance and counseling procedures were similar across schools in the area of study. For example, even school decried lack of personnel to assist in identification of EBD learners for proper placement. Furthermore, there were no resources to facilitate teachers to put the identified learners on proper plan to assist in improving their academic performance.